Correlation between the California Mastitis Test (CMT) and somatic cells count on milk from Murrah buffalo cows - Jorge, André Mendes [UNESP]; Andrighetto, Cristiana; Strazza, Mara Regina Barzon [UNESP]; De Correa Cássia, Rita [UNESP]; Kasburgo, Débora Galhardo [UNESP]; Piccinin, Adriana [UNESP]; Victória, Cassiano [UNESP]; Domingues, Paulo Francisco (Elsevier, 2005)
The objective of this trial was to investigate correlations among the California Mastitis Test, somatic cells count (SCC), and milk yield. Milk samples were collected from thirty-eight Murrah buffalo cows in the years of 2002 and 2003. Milking management included cleaning teats with individual paper towel followed by attachment of the milk units in cows that were milked once daily. The CMT was done immediately after teat cleaning and collected milk samples were sent to the laboratory for determination of SCC using a Somacount 300. Correlations including variables such as SCC, CMT, milk yield, and percentages of fat, protein, and total solids were done using SAEG (1997). Somatic cells count averaged 63.380 cells/mL while average milk production and milk production adjusted for 270 days were 4.07 ± 1.3 kg and 1214.25 ± 293.54 kg, respectively. No significant correlations between milk yield and SCC and milk yield and CMT were observed in this study. However, a positive and significant correlation (0.53) between SCC and CMT was found.
Correlação entre o California Mastitis Test (CMT) e a contagem de células somáticas (CCS) do leite de búfalas Murrah
Keywords: California Mastitis Test; Milk yield; Murrah; Somatic count cells